Peningkatan Hasil Belajar Mahasiswa Melalui Implementasi Model Pembelajaran STAD dan JIGSAW Ditinjau dari Gaya Belajar - Mendrofa, Operianus; Zai, Eka Periaman; Lase, Indah Wijaya (Jurnal Pendidikan Matematika : Judika Education, 2024)
The purpose of this study was to determine; 1) differences in learning outcomes of students who are taught with the STAD and JIGSAW learning models, 2) differences in learning outcomes reviewed by learning styles, 3) interactions between learning models and learning styles on learning outcomes. The population consisted of 2nd semester PGSD students with a sample size of 92 people. Data collection techniques used observation sheets and posttests. Research data were analyzed using a two-way ANOVA approach with the help of SPSS version 27. The results of the study indicate that 1) there are significant differences in learning outcomes taught with the STAD and JIGSAW learning models, 2) there are significant differences in learning outcomes when viewed from learning styles, 3) there is interaction between learning models and learning styles on learning outcomes. This study reveals that there are significant differences in the learning outcomes of students taught with the STAD and JIGSAW learning models, indicating that the effectiveness of the two models is different. Conclusion, The selection of learning models and identification of student learning styles are very important in improving learning outcomes Keywords: STAD and JIGSAW, Learning Styles and Learning Outcomes.